Socio-demographic determinants of knowledge, attitude and practices towards food safety among Lebanese population during the economic crisis: a cross-sectional study - Rana El Haidari; Fatima Fahes; Fatima Makke; Fatima Nouredine; Kassem Baydoun; Samir Mansour; Abbas Hoballah (BMC, 2022)
Abstract Background Lebanon has been gripped by an economic crisis and the local currency has lost more than 90% of its value; besides, a lack of consistent electricity supply which has contributed to rising concerns about food safety especially among households. This study aimed to assess Lebanese society knowledge, attitude and practice towards food safety during the economic crisis. Methods A cross-sectional study was conducted in Lebanon between September 5 and January 30, 2021. Data was collected through an online survey that included information on socio-demographic characteristics, knowledge, attitude and practice of Lebanese consumers towards food safety. Two multivariate regression models were performed on the knowledge and practices as a dependent variable. 95% confidence interval was calculated. All tests were two-sided and statistical significance was set at p-value < 0.05. Results The majority of participants had good knowledge regarding food safety (74.9%) while more than half of the respondents adopted good preventive practices (62.8%). Multivariate regression of factors associated with good knowledge regarding food safety showed married participants (adjusted OR = 2.1; p < 0.0001), who had university degree and above (adjusted OR = 2.0; p < 0.0001), and who had income < 1,500,000 LBP (adjusted OR = 1.7; p < 0.0001) had a significantly good knowledge score compared to their counterparts. Finally, participants aged more than 35 years old and who had income higher than 1,500,000 LBP (adjusted OR = 1.8; p < 0.0001 and adjusted OR = 1.9; p = 0.01 respectively) were positively associated to good practice towards food safety. Conclusion This study offers useful insights into the knowledge, attitude and practices of Lebanese consumers towards food safety during the economic crisis.